2011
DOI: 10.3389/fpsyt.2011.00029
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Opiate Exposure in the Female Rat Induces Subtle Alterations in Maternal Care and Transgenerational Effects on Play Behavior

Abstract: The non-medical use of prescription opiates, such as Vicodin® and MSContin®, has increased dramatically over the past decade. Of particular concern is the rising popularity of these drugs in adolescent female populations. Use during this critical developmental period could have significant long-term consequences for both the female user as well as potential effects on her future offspring. To address this issue, we have begun modeling adolescent opiate exposure in female rats and have observed significant tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 95 publications
6
48
1
2
Order By: Relevance
“…Previous studies showed sex-differential behavior in the offspring of adolescent morphine-exposed rats (Byrnes, 2005;Johnson et al, 2011). Female offspring developed anxiety-like behavior, whereas male offspring demonstrated significantly enhanced morphine sensitization (Byrnes, 2005;Johnson et al, 2011). By contrast, in our study, both male and female offspring demonstrated anxiety-like behavior in the EPM and OFT procedures.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Previous studies showed sex-differential behavior in the offspring of adolescent morphine-exposed rats (Byrnes, 2005;Johnson et al, 2011). Female offspring developed anxiety-like behavior, whereas male offspring demonstrated significantly enhanced morphine sensitization (Byrnes, 2005;Johnson et al, 2011). By contrast, in our study, both male and female offspring demonstrated anxiety-like behavior in the EPM and OFT procedures.…”
Section: Discussioncontrasting
confidence: 87%
“…In the present study, adult morphine exposure did not affect general parameters perhaps because the animals had reached full sexual maturity when the drug was administered. Previous studies showed sex-differential behavior in the offspring of adolescent morphine-exposed rats (Byrnes, 2005;Johnson et al, 2011). Female offspring developed anxiety-like behavior, whereas male offspring demonstrated significantly enhanced morphine sensitization (Byrnes, 2005;Johnson et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…However, no study has investigated TNF-α or other cytokine levels in offspring of parents that were exposed to morphine. Several studies have revealed that opioids and opioid receptor expression may be altered in the offspring of parents with a background of morphine consumption (36,40,50). In fact, some consequences of chronic opioid consumption could be transgenerationally transmitted from parents to offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, a premating morphine exposure regimen (prior to pregnancy) had no effect on maternal behavior (Yim et al, 2006;Johnson et al, 2011) but induced long-term effects in offspring. In line with this finding, the female offspring of dams exposed to morphine during puberty displayed increased anxiety-like behavior both in the elevated plus-maze (EPM) and in a novel environment, possibly due to altered prolactin regulation (Byrnes, 2005a).…”
Section: Animal Studiesmentioning
confidence: 99%